Producción de un documental cultural, para la visibilización y difusión de los artesanos que confeccionan la ropa para los disfrazados de las fiestas del niño de Isinche del cantón Pujilí - Mueces Fauta, Willams Rodrigo (2016)
The objective of this investigation is to document and to give to know the job that elaborate the different artisans and make the typical suits for the characters that intervene in the processions and Niño de Isinche’s parties, it is sustained in the creation of an audiovisual cultural documentary for the visibilization of the laborious job that they make for the obtaining of the suits that later they are used in the festivities on December and at the beginning of every year, with the made investigations it was detected that most of people that visit the sanctuary of the Niño de Isinche, don’t know the work that the artisans carry out to achieve these wonderful pieces of dressing, through this we seek the revaluation of the cultural identity that transmit these suits being a fundamental part for the development of Pujilí canton and the Isinche neighborhood.